2003
DOI: 10.1038/sj.onc.1206101
|View full text |Cite
|
Sign up to set email alerts
|

Detailed computational study of p53 and p16: using evolutionary sequence analysis and disease-associated mutations to predict the functional consequences of allelic variants

Abstract: Deciding whether a missense allelic variant affects protein function is important in many contexts. We previously demonstrated that a detailed analysis of p53 intragenic conservation correlates with somatic mutation hotspots. Here we refine these evolutionary studies and expand them to the p16/Ink4a gene. We calculated that in order for 'absolute conservation' of a codon across multiple species to achieve Po0.05, the evolutionary substitution database must contain at least 3(M) variants, where M equals the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 21 publications
5
91
0
Order By: Relevance
“…It has been shown previously that disease mutations are generally not distributed at random among amino acid sites within genes (for example, Botstein & Risch, 2003;Greenblatt et al 2003;Miller & Kumar, 2001;Mooney & Klein, 2002;Notaro et al 2000). Instead, disease-causing mutations are generally overabundant at evolutionarily conserved sites.…”
Section: Testing For the Distribution Of Human Mutations Using The Inmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that disease mutations are generally not distributed at random among amino acid sites within genes (for example, Botstein & Risch, 2003;Greenblatt et al 2003;Miller & Kumar, 2001;Mooney & Klein, 2002;Notaro et al 2000). Instead, disease-causing mutations are generally overabundant at evolutionarily conserved sites.…”
Section: Testing For the Distribution Of Human Mutations Using The Inmentioning
confidence: 99%
“…Recent literature clearly underscores the importance of understanding human disease mutations from an evolutionary perspective (Botstein & Risch, 2003). Therefore, this second test is necessary because there is a known overabundance of disease mutations at evolutionarily conserved amino acid sites (Greenblatt et al 2003;Miller & Kumar, 2001;Mooney & Klein, 2002;Notaro et al 2000), thus illustrating the importance of conserved residues in the proper functioning of protein products.…”
Section: Introductionmentioning
confidence: 99%
“…The deleted sequence is located in the first ankyrin repeat and encodes an evolutionarily conserved 6 amino acids (LEAGAL). 28 Deletions and mutations affecting these amino acid have been reported in melanomas and other cancers and shown to significantly affect the CDK-and cell cycleinhibitory activities of p16…”
Section: Mutation Analysis and Expression Of Wild-type Ink4amentioning
confidence: 99%
“…This portion of ARF was believed to be dispensable because ectopic expression of the N-terminal half of ARF is sufficient to fulfill all known functions of full-length ARF, 6,8,11 and the chicken ortholog p7 ARF , which lacks the exon2-derived C-terminal half, displays most, if not all, of the known functional attributes of its mammalian counterparts. 12 Nevertheless, why the 5' portion of the exon2 that is shared by p16 and ARF is preferentially attacked by cancer mutations, 3,[13][14][15] especially by those that affect only ARF but not p16, has remained unexplained. Genetic evidences have demonstrated that mice lacking functional ARF, Mdm2 and p53 together are more tumor-prone than those lacking both Mdm2 and p53, indicating that ARF has growth inhibitory functions independent of Mdm2 and p53.…”
mentioning
confidence: 99%